Soil Temperature Regime at Ahmedabad - Sharan, Girja; Jadhav, Ratan (Journal of Agricultural Engineering, 2002)
A 3-m deep probe with five PT 100 temperature sensors was installed at the campus of Indian Institute of Management, Ahmedabad in August, 1999 to monitor temperature at various depths. Hourly values from all the sensorS were noted one day in each month for a year. The diurnal and seasonal variations of temperature at different depths in soil have been observed in order to determine the level suitable for installation of earth tube heat exchangers.